2017
DOI: 10.1080/00140139.2017.1314554
|View full text |Cite|
|
Sign up to set email alerts
|

Combined exposures of whole-body vibration and awkward posture: a cross sectional investigation among occupational drivers by means of simultaneous field measurements

Abstract: The combined exposure of WBV and awkward posture can be described in terms of the daily vibration exposure and the index for awkward posture. This facilitates work place assessments and future research in this area. Practitioner Summary: For the first time, quantitative measures combining whole-body vibration and awkward posture exposures have shown to correlate with the occurrence of low back pain significantly. This validates the proposed quantities and measurement methods, which facilitate workplace assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The findings of the study may imply that the difference of postural load may be the main reason for the difference of the prevalence of LBP among different types of workers. In addition, the results of the logistic regression model and SEM showed that job tenure and vibration were positively associated with LBP, which was consistent with previous studies [26,27,53]. A plausible hypothesis is that the higher risk of LBP in workers with longer employment length is a consequence of a longer time exposed to occupational risk factors compared to those who have less employment length [54].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the study may imply that the difference of postural load may be the main reason for the difference of the prevalence of LBP among different types of workers. In addition, the results of the logistic regression model and SEM showed that job tenure and vibration were positively associated with LBP, which was consistent with previous studies [26,27,53]. A plausible hypothesis is that the higher risk of LBP in workers with longer employment length is a consequence of a longer time exposed to occupational risk factors compared to those who have less employment length [54].…”
Section: Discussionsupporting
confidence: 89%
“…Results of studies also have provided evidence for the correlation between psychological factors and biomechanical factors [24,25]. Some studies have shown that vibration also plays an important role in the occurrence and development of LBP [26,27]. These risk factors are not independent and may interact with each other, and the complex relationships between these factors are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the small number of measurements made and the lack of power of the study. The two other essential factors responsible for low back pain, namely constraining postures and heavy loads are not studied in this work [20,21]. Moreover, in this study, even if driving excavators remains the main task, drivers are also versatile and also perform maneuver tasks in support of their colleagues with very constraining handling and postures.…”
Section: Discussionmentioning
confidence: 90%
“…Two prior studies have measured posture among drivers with direct methods (Hermanns et al 2008;Raffler et al 2017). However, none of these studies presented ROMs as a direct result of driving over obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…Inertial measurement units (IMUs), common in navigation and now common in fitness trackers, may provide new information about postural loads and can be used synchronously to also measure acceleration in the seat of the vehicle as well as the body. Similar systems have been used to measure the posture of drivers in different types of vehicles (Hermanns et al 2008;Raffler et al 2017). However, neither of these studies presented postural loads as a result of mechanical shocks or within forestry.…”
Section: Introductionmentioning
confidence: 99%